Desenvolvimento de materiais para a detecção e degradação do bisfenol A e seus intermediários de reação - Goulart, Lorena Athie (2016)
In this study, tungsten oxide and copper composites were developed for making applied anodes in fotoelectrolysis of bisphenol A (BPA) and electrochemical sensors composed of carbon nanotubes (CNTs) and metal nanoparticles (NPM) for the detection of BPA and its reaction intermediates such as hydroquinone (HQ), catechol (CC) and phenol (Phe). The sensors were obtained by casting method on a glassy carbon surface and the quantitation of molecules of interest was carried out by pulsed techniques using the standard addition method. Different methods of functionalization, and the influence of CNTs sizes were investigated for the determination of BPA. CNTs samples with 20-170 nm in diameter were functionalized in HNO3 solution 5.0 mol L-1 solution and sulfonitric (3H2SO4: 1HNO3). The size and functionalization directly affect the oxidation of BPA and smaller diameter CNTs with improved sensitivity and showed the low limit of detection (LOD) of 8.4 × 10-8 mol L-1. The simultaneous determination of HQ, CC, and BPA was made with CNTs sensor modified with nickel oxide nanoparticles (NiO/MWCNT/GCE). The deposition of NiO was made by cyclic voltammetry (CV) and were evaluated the concentration of the nickel solution and the number of cycles. The best results were obtained when NiO was deposited in a solution of 8.0 mmol L-1 Ni(NO3)2 and 40 cycles. The analytical curves showed an excellent linear response and the LODs for the simultaneous determination of BPA, HQ and CC were 2.8 × 10-8 mol L-1, 2.7 × 10-8 mol L-1 and 5.9 × 10-8 mol L-1, respectively. Silver nanoparticles (AgNPs) were also incorporated in the films of MWCNT/GCE by CV. The AgNPs/MWCNT/GCE sensor showed good stability and reproducibility and has been successfully applied to the simultaneous determination of HQ, CC, BPA and Phe in tap water samples. Morphological characterization of the developed sensor was performed by scanning electron microscopy (SEM) and electrochemical characterization was made by CV and electrochemical impedance spectroscopy. Tungsten oxide films doped with copper (WO3-Cu) obtained by the modified sol-gel method were used in the studies photoelectrolysis BPA. The doping with Cu increased six fold the value of the photocurrent density of the material compared to the WO3. The characterization of the synthesized anode was made by techniques of X-ray diffraction, SEM and energy dispersive microanalysis (EDX). The monitoring of the decay of the concentration of BPA and the formation of intermediates generated during the photoelectrolysis was made by electrochemical sensors based on CNTs/NiO and UV-Vis absorption. The results of the total organic carbon content showed 75% of BPA was degraded and it was found that it is possible to monitor the BPA of degradation process and the formation of reaction intermediates using sensors developed in this work.